ShAn: An easy-to-use tool for interactive and integrated variant annotation - Rathinakannan VS; Schukov HP; Heron S; Schleutker J; Sipeky C (PUBLIC LIBRARY SCIENCE, 2022)
Motivation
Annotation of large amounts of generated sequencing data is a demanding task. Most of the currently available robust annotation tools, like ANNOVAR, are command-line based tools which require a certain degree of programming skills. User-friendly tools for variant annotation of sequencing data with graphical interface are under-represented.
Results
We have developed an interactive application, which harnesses the easy usability of R Shiny and combines it with the versatile annotation features of ANNOVAR. This application is easy to use and gives comprehensive annotations for user supplied vcf files using multiples databases. The output table contains the list of variants and their corresponding annotation presented within the graphical interface. In addition, the annotation results are downloadable as text file.